Linguistic Contrasts and Social Integration: Pedagogical Challenges for Albanian and Slavic Language Learners - Morina, Qendrim; Millaku, Shkelqim; Berisha, Naim (European Journal of Social Science Education and Research, 2026)
The definite articles in Albanian are (-i, -u, -a, -ja, -t (ë), -s(ë), -n(ë) as in the examples mal -i, ujk -u, fushë -a or in other languages are as mal -i, ujk -u, fushë -a, Romanin: lup (ujk), lupul, munte, (mal), muntele, apo (ujë); Bullganian: kon. (kalë), kojot, voda (ujë), vodata; gr. lýkos (ujk), vounó (mali), neró (uji), πεδίο pedío (fusha). The article with Adjective e.g. i mirë, i shpejtë, i ngadalshëm; the article genitive nouns e.g. mishi i lopës, lulja e blinit, Fakulteti i Filologjisë, Universiteti i Sofjes; at the neuter nouns e.g. të folurit, të punuarit, të ngrënët; the female nouns of origine participle adjective e.g. e folmja, e ardhmja; number e.g. i parë, i dytë, i tretë; the article of demonstrative pronouns e.g. e tillë, e tillë; the article of interrogative pronouns e.g. i sati; possessive pronouns e.g. e mi, e t’u, i tij, i saj; the articles od weeks day e.g. e hënë, e marte; the article of the nouns saints or ethnic e.g. i Shënkolli, i Shëngjergji - i mirditas, i dukagjinas; the article of the nouns kinship e.g. i biri, e bija, i ati, e ëma; the article of relative pronouns e.g. i cili, e cila, të cilët, të cilat and the article of indefinite pronouns e.g. të gjithë, të tërë. In Albanian language the days of the week are with indefinite article, but in Slave languages it is not as in: në shqip (e hënë), gr. Δευτέρα deftéra, bullg. Понеделник ponedelnik, serb. Понедељак ponedeljak, croat. ponedjeljak, maced. понеделник ponedelnik; rus. Понедельник ponedel’nik.